Anxiety in Children and Adolescents with Epilepsy - Dunn, David W.; Walsh, Kelda (Journal of Pediatric Epilepsy, 2018)
Anxiety is a common comorbidity in children with epilepsy, though often overlooked and undertreated. Fear and worry are common reactions of children with epilepsy and their parents. Risk factors are multiple and include demographical, epilepsy-related, genetic, and family variables. Anxiety negatively affects health-related quality of life (QOL) and may contribute to poor seizure control. Appropriate treatment of anxiety in children with epilepsy should follow practice guidelines developed for treatment of anxiety in children without epilepsy and consist of education, counseling, and potentially psychopharmacology.
Keywords: childhood epilepsy; anxiety disorders; emotional comorbidity in epilepsy